Animal antimicrobial peptides: an overview - Andreu, D; Rivas, L (Biopolymers, 1998)
Antibiotic peptides are a key component of the innate immune systems of most multi-cellular organisms. Despite broad divergences in sequence and taxonomy, most antibiotic peptides share a common mechanism of action, i.e., membrane permeabilization of the pathogen. This review provides a general introduction to the subject, with emphasis on aspects such as structural types, post-translational modifications, mode of action or mechanisms of resistance. Some of these questions are treated in depth in other reviews in this issue. The review also discusses the role of antimicrobial peptides in nature, including several pathological conditions, as well as recent accounts of their application at the preclinical level.